The Impact Of Bankung Digitalization And Productive Credit Distribution On The Performance Of Micro,Small and Medium Enterprises ( Msmes) During The 2023–2025 Period - M. Yahya Azzahid; Nun Tupa; Moh. Abd Rahman (CV Putra Publisher, 2026)
This study aims to analyze the impact of banking digitalization and productive credit distribution on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia during the period 2023–2026. The rapid development of digital technology in the banking sector has introduced various digital financial services that facilitate financing access, transactions, and financial management for MSMEs. Meanwhile, productive credit serves as an essential instrument in improving business capacity, productivity, and competitiveness. This research employed a quantitative approach using an explanatory research design. The sample consisted of 200 MSME owners who utilized digital banking services and received productive loans from banking institutions across Indonesia. Data were analyzed using multiple linear regression supported by statistical software. The findings revealed that banking digitalization had a positive and significant effect on MSME performance, contributing 38.4% to performance improvement. Productive credit distribution also had a positive and significant impact, contributing 42.7%. Simultaneously, both variables explained 68.5% of the variance in MSME performance. These findings indicate that enhancing access to digital banking services and optimizing productive credit programs can become effective strategies for strengthening sustainable MSME growth. This study provides implications for policymakers, banking institutions, and business actors in formulating strategies to strengthen the national digital economic ecosystem and improve financial inclusion among MSMEs.